KESETIMBANGAN ADSORPSI ION LOGAM CHROM VI OLEH ZEOLIT PADA BERBAGAI UKURAN PARTIKEL - Syarifah Aini; Supratikno _ (IST AKPRIND Yogyakarta, 2018)
The waste of heavy metal such as chrom metal ion needs further process by certain technics. One of them is adsorbent one by applying the equilbrium principle of adsorption. Zeolite is the suitable adsorbent to use to absorb the metal ion of chrom. The purpose of the study is to determine the suitable model for equilbrium adsorption of metal ion of chrom VI by zeolite together with its parameter values and to know the maximum power absorbtion of zeolite toward metal ion of chrom VI. The production of the solution of metal ion of chrom VI in various concentration such as concentration of 10 ppm, 30 ppm, 50 ppm, and 70 ppm. Each of the solution is added by 40 gram of zeolit and stirred for 30 minutes then filtered and the filtrat is analyzed by spectrophotometer. The experiment is conducted by the various particle size of zeolite such as 50 mesh, 100 mesh, and 170 mesh. The study uses the method of application model of isoterm adsorption equilbrium that covers 5 equations that is Linier Adsorption (Henry’s Law), Isotherm Adsorption of Freundlich, Isotherm Adsorption of Langmuir, Isotherm of Brunauer-Emmett-Teller (BET), the Equation of Sigmoidal Chapman. From these five models then data fitting is conducted to find the model that closer to the data. Data matching is conducted by minimizing that is run by Matlab program. The result of study shows that the suitable and closer model is the model of Isotherm adsorbtion of Freundlich in its equilbrium constant 0,0018 l/g. The maximum concentration of metal ion of chrom VI absorbed by zeolite is 5,6402 mg/g to the 170 mesh of particle size. The study can be concluded that the smaller size of particle of adsorbent the bigger material concentration absorbed.